2020
DOI: 10.21203/rs.2.21902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of pre-transplant dialysis modality on the outcome and health-related quality of life of patients after simultaneous pancreas-kidney transplantation

Abstract: Background Simultaneous pancreas-kidney transplantation (SPKT) profoundly improves the Health-related quality of life (HRQoL) of the recipients. However, the influence of the pre-transplant dialysis modality on the success of the SPKT and post-transplant HRQoL is still unknown. Methods We analyzed the surgical outcome, long-term survival, as well as HRQoL of 83 SPKTs that were performed between 2000 and 2016 in our Hospital. Prior to transplant, 63 patients received hemodialysis (HD) and 19 patients received p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…37 More recent studies compared QoL before and after SPK and confirmed an improvement after transplant. [38][39][40][41] Improved metabolic control was also associated with better health-related and diabetes-related QoL in both islet transplant alone and islet-after-kidney transplantation. 17,42 More studies are needed in the current era of modern insulin-delivery technology to compare patient-reported outcomes in pancreas versus islet transplant recipients transplanted simultaneously with or after the kidney, as well as KTA using standardized and validated surveys.…”
Section: Quality Of Lifementioning
confidence: 97%
“…37 More recent studies compared QoL before and after SPK and confirmed an improvement after transplant. [38][39][40][41] Improved metabolic control was also associated with better health-related and diabetes-related QoL in both islet transplant alone and islet-after-kidney transplantation. 17,42 More studies are needed in the current era of modern insulin-delivery technology to compare patient-reported outcomes in pancreas versus islet transplant recipients transplanted simultaneously with or after the kidney, as well as KTA using standardized and validated surveys.…”
Section: Quality Of Lifementioning
confidence: 97%